(untitled) (Texas Journal of Medical Science, 2025)
Anemia and overweight represent a growing double burden of malnutrition among preschool children worldwide. Iron-deficiency anemia remains highly prevalent due to insufficient intake of micronutrients, while overweight is increasing as a result of high-calorie, nutrient-poor diets and reduced physical activity. Despite appearing metabolically opposite, both conditions frequently coexist, leading to impaired growth, reduced cognitive performance, and long-term metabolic complications.